The Potential of Using Educational Technologies to Meet the Needs of Agriculture Graduates - Naana O. Nti; Blannie E. Bowen (Journal of Applied Communications, 1998)
Distance education is a useful tool for agricultural and extension education departments in the delivery of courses to students. However, faculty, instructional designers, and agricultural communicators must understand the needs of learners in order for courses to be effective. A mail survey was conducted to assess the demand by agricultural science graduates for courses delivered by distance education and their skills and experiences in using distance education technologies. The majority of agricultural science graduates were interested in taking courses by distance education for professional development and advanced degrees. Few graduates had experiences with distance education but most were familiar with most of the distance education technologies.